The Formation of Intermediate Product I in a Purified System The Role of Factor IX or of its Precursor and of a Hageman Factor-PTA Fraction - Yin, E. T; Duckert, F (Thrombosis and Haemostasis, 1961)
1. The role of two clot promoting fractions isolated from either plasma or serum is studied in a purified system for the generation of intermediate product I in which the serum is replaced by factor X and the investigated fractions.2. Optimal generation of intermediate product I is possible in the purified system utilizing fractions devoid of factor IX one-stage activity. Prothrombin and thrombin are not necessary in this system.3. The fraction containing factor IX or its precursor, no measurable activity by the one-stage assay method, controls the yield of intermediate product I. No similar fraction can be isolated from haemophilia B plasma or serum.4. The Hageman factor — PTA fraction shortens the lag phase of intermediate product I formation and has no influence on the yield. This fraction can also be prepared from haemophilia B plasma or serum.